The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/saj2.20462
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil health indicators to long‐term dairy manure in a semiarid irrigated cropping system

Abstract: Dairy manure fertilization is an important practice to return nutrients to agricultural soils, but there is limited knowledge regarding the effect of manure on soil health metrics in semiarid irrigated row crops. The objective of this research was to determine how long-term dairy manure application affects biological and chemical indicators of soil health in a field experiment in southern Idaho. The treatments were no fertilizer, inorganic fertilizer (IF), and dairy manure applied annually or biennially at rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…MinC tends to be more sensitive to manure use relative to POXC or SOM (Hurisso et al., 2016). Applying manure had no effect on POXC in some studies (Jokela et al., 2009; Wienhold, 2005), but others found greater POXC associated with manure use (Dungan et al., 2022; Min et al., 2003; Mirsky et al., 2008). On farms in North Carolina, both soil organic C and soil test biological activity were 50%–55% greater in fields receiving organic amendments (Franzluebbers, 2020a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…MinC tends to be more sensitive to manure use relative to POXC or SOM (Hurisso et al., 2016). Applying manure had no effect on POXC in some studies (Jokela et al., 2009; Wienhold, 2005), but others found greater POXC associated with manure use (Dungan et al., 2022; Min et al., 2003; Mirsky et al., 2008). On farms in North Carolina, both soil organic C and soil test biological activity were 50%–55% greater in fields receiving organic amendments (Franzluebbers, 2020a).…”
Section: Resultsmentioning
confidence: 97%
“…MinC tends to be more sensitive to manure use relative to POXC or SOM (Hurisso et al, 2016). Applying manure had no effect on POXC in some studies (Jokela et al, 2009;Wienhold, 2005), but others found greater POXC associated with manure use (Dungan et al, 2022;Min et al, 2003;Mirsky et al, 2008).…”
Section: Manure Use In Annual Rotationsmentioning
confidence: 94%
“…In the present study, as manure application rates increased, there was a concurrent increase in soil N and P potentially enhancing microbial processes. In 2019, Dungan et al (2022) evaluated a variety of soil health indicators in soils from the present study. They reported that potentially mineralizable N, microbial biomass N, and potential ammonia oxidation rates, as well as a variety of other biological indicators, increased with increasing manure application rates with both annual and biennial applications.…”
Section: Discussionmentioning
confidence: 99%
“…These changes can affect N immobilization and mineralization. Long‐term additions of manure also increase microbial abundances and enhance soil enzyme activities that impact cycling of C and N in soils (Ashraf et al., 2020; Dungan et al., 2022; Masunga et al., 2016; Wang et al., 2022). Many studies have evaluated the effects of a one‐time application of manure; however, long‐term application of manure may enhance the residual N pool that is available for mineralization in subsequent years, and therefore short‐term studies may underestimate future plant‐available N from manure (Mallory et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted to assess the effects of cattle manure (beef or dairy) on soil health indicators (chemical and biological) in irrigated semiarid cropping systems (Dungan et al, 2022;Elzobair et al, 2016;Lupwayi et al, 2019;Miner et al, 2020). In southern Idaho, Dungan et al (2022) found that enzyme activities and N transformation rates were significantly greater in soils amended with high rates of dairy manure for several years. In the semiarid environment of Lethbridge, Canada, Lupwayi et al (2019) reported that increased enzyme activities could be detected decades after the last beef cattle manure application, with significantly greater microbial biomass and enzyme activity under irrigated versus rainfed conditions.…”
Section: Introductionmentioning
confidence: 99%